2016
DOI: 10.1186/s12889-016-3836-9
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary lifestyle and its associated factors among adolescents from public and private schools of a Brazilian state capital

Abstract: BackgroundAdolescence is a transition stage between childhood and adulthood and is an important phase for the acquisition of future lifestyles, including the practice of physical activity (PA). The prevalence of sedentary lifestyle in adolescents is often high, creating the need for studies addressing the practice of PA and its associated factors for a better understanding of the phenomenon and possible interventions that would encourage positive changes.MethodsCross-sectional study of a representative sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
2
19
1
1
Order By: Relevance
“…Regarding the components of the ASA score, the majority of them were higher in males than in females, thus suggesting that male students might have greater knowledge and practice healthy habits. In accordance with these findings, other recent studies have shown overweight and sedentary lifestyles to be more prevalent among female students compared to male students [38,39]. To date, no studies have analyzed gender differences of self-care agency in university students, though several studies conducted in adults support our observations.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the components of the ASA score, the majority of them were higher in males than in females, thus suggesting that male students might have greater knowledge and practice healthy habits. In accordance with these findings, other recent studies have shown overweight and sedentary lifestyles to be more prevalent among female students compared to male students [38,39]. To date, no studies have analyzed gender differences of self-care agency in university students, though several studies conducted in adults support our observations.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that girls were more likely to report a sedentary lifestyle and were less likely to be involved in group exercise and to walk to and from school. Similar findings were reported in a study done in Brazil, where girls were more likely to report a sedentary lifestyle [31]. A Japanese study showed that walking to school can help combat obesity [32].…”
Section: Discussionsupporting
confidence: 85%
“…Evidence substantiates the presence of correlation between sedentism and the increased chances of cardio-metabolic risks among different population (25)(26)(27). Since University academic employees are more likely at risk of sedentism, occupational status, income, and other lifestyle changes, it is crucial to study cardio-metabolic risks and its associated factors among this population..…”
mentioning
confidence: 65%